Porous silicon carbon negative electrode material and preparation method and application thereof

By using a porous silicon-carbon structure in the negative electrode material of lithium-ion battery and using the elemental sulfur sublimation method to create a cavity structure, the problems of silicon volume expansion and insufficient conductivity are solved, and the cycle stability and rate performance of the battery are significantly improved.

CN119324206APending Publication Date: 2025-01-17LIYANG TIANMU PILOT BATTERY MATERIAL TECH CO LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202310879069.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-17
Publication Date
2025-01-17

AI Technical Summary

Technical Problem

The existing lithium-ion battery negative electrode material silicon has large mechanical stress, crushing and powdering due to volume expansion, which affects the circulation ability and Coulomb efficiency, and has poor conductivity, limiting the rate performance.

Method used

The porous silicon-carbon negative electrode material is used to coat the porous carbon layer and hollow layer on the core of the silicon/carbon composite material, and sublimate element sulfur as a template to create a cavity structure to alleviate volume expansion and improve conductivity.

Benefits of technology

It significantly improves the cycle stability and rate performance of the negative electrode of lithium-ion battery, enhances electrochemical performance, and extends battery life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119324206A_ABST
    Figure CN119324206A_ABST
Patent Text Reader

Abstract

The embodiment of the invention relates to a porous silicon carbon negative electrode material and a preparation method and application thereof. The porous silicon-carbon negative electrode material comprises a silicon / carbon composite material core, a porous carbon layer coating the core, and a hollow layer between the silicon / carbon composite material core and the porous carbon layer, the hollow layer is of a cavity structure manufactured after sublimation by taking elemental sulfur as a template; according to the porous silicon-carbon negative electrode material disclosed by the invention, the cavity manufactured after sublimation by taking elemental sulfur as a template between the silicon / carbon composite material core and the porous carbon layer is used as the hollow layer, and the hollow layer and the porous carbon layer can effectively relieve volume expansion of silicon and improve the cycling stability of a silicon negative electrode; meanwhile, the carbon material and the porous carbon layer in the inner core can improve the ion and electron conductivity and enhance the rate capability of the silicon negative electrode.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of new energy materials, and in particular to a porous silicon-carbon negative electrode material and a preparation method and application thereof. Background Art

[0002] With the rapid development of large-scale energy storage technology, electric vehicles, and various electronic devices, the energy density of existing commercial lithium-ion battery systems can no longer meet the growing needs of these fields. Therefore, the development of high-performance, high-specific capacity electrodes is an urgent need to solve this problem. For the negative electrode, silicon is one of the most promising lithium-ion battery materials because its theoretical capacity is as high as 4200mAh / g, which is about 10 times that of graphite electrode (372mAh / g). However, a dramatic volume expansion (400%) occurs during the alloying / dealloying process of the silicon negative electrode. The dramatic volume expansion will produce huge mechanical stress, which often causes the silicon negative electrode material to break and pulverize, thereby causing the battery cycle capacity to decay. In addition, due to the dramatic volume expansion, an unstable solid electrolyte interface (SE I) film is easily formed on the silicon negative electrode material, which will cause a large amount of irreversible consumption of the electrolyte, resulting in low coulombic efficiency of the silicon negative electrode material. In addition, due to the poor electronic conductivity of silicon itself, it is not conducive to the rapid transmission of electrons and affects the normal performance of the capacity of silicon-based materials, making silicon-based negative electrode materials have poor rate performance.

[0003] In response to these problems, many patents have been published for the use of template etching to prepare silicon / carbon composites with yolk-shell or hollow core-shell structures. Silicon / carbon composites with this structure can not only adapt to the volume changes of silicon during the cycle, but also form a stable SEI layer, while improving conductivity. The template etching method often uses hydrofluoric acid to etch oxide templates such as silicon dioxide (SiO2) to create cavities between silicon and carbon. This process requires multiple steps of long-term acid immersion and water cleaning processes. The preparation process is complicated, dangerous and not green and environmentally friendly. Therefore, a more suitable strategy for preparing porous silicon / carbon composites as negative electrodes for lithium batteries is still under continuous research. Summary of the invention

[0004] The purpose of the present invention is to provide a porous silicon-carbon negative electrode material and a preparation method and application thereof. The porous silicon-carbon negative electrode material of the present invention can effectively alleviate volume expansion and improve the conductivity of the material, and show excellent cycle performance and rate performance.

[0005] To this end, in a first aspect, an embodiment of the present invention provides a porous silicon-carbon negative electrode material, comprising: a silicon / carbon composite material core, a porous carbon layer coated on the outside of the core, and a hollow layer between the silicon / carbon composite material core and the porous carbon layer;

[0006] The hollow layer is a cavity structure manufactured by sublimation using elemental sulfur as a template; the hollow layer and the porous carbon layer are used together to alleviate the volume expansion of silicon.

[0007] Preferably, the silicon / carbon composite material core comprises a silicon source and a carbon material;

[0008] The silicon source includes: a combination of one or more of nano silicon powder, micro silicon powder, and silicon monoxide;

[0009] The carbon material includes: a combination of at least one or more of nanographite, micrographite, hard carbon, soft carbon, single-walled carbon nanotubes, multi-walled carbon nanotubes, graphene, and graphyne.

[0010] More preferably, the particle size of the silicon source is 1 to 1000 nm.

[0011] Preferably, the porous carbon layer is obtained by carbonizing a pyrolytic carbon source;

[0012] The pyrolysis carbon source includes: a combination of at least one or more of glucose, sucrose, starch, asphalt, polydopamine, phenolic resin, polyacrylonitrile, polypyrrole, polypyridine, polyaniline, and ethyl cellulose.

[0013] In a second aspect, an embodiment of the present invention provides a method for preparing the porous silicon-carbon negative electrode material according to the first aspect, the preparation method comprising:

[0014] The silicon source and the carbon material are ultrasonically mixed in a solvent according to a certain mass ratio, and vacuum filtered to obtain a silicon / carbon composite material core;

[0015] A certain mass of elemental sulfur is dissolved in a certain amount of carbon disulfide to obtain a mixed solution, and then the silicon / carbon composite material core is added to the mixed solution and continuously stirred until all the carbon disulfide is volatilized to obtain a sulfur-coated silicon / carbon composite material;

[0016] Pyrolyzing the sulfur-coated silicon / carbon composite material to coat the sulfur-coated silicon / carbon composite material to obtain a carbon-coated composite material;

[0017] The composite material coated with the carbon source is subjected to low-temperature desulfurization and high-temperature carbonization treatment under an inert atmosphere to obtain a porous silicon-carbon negative electrode material; wherein the calcination temperature of the low-temperature desulfurization is 210-260°C; and the calcination temperature of the high-temperature carbonization treatment is 600-900°C.

[0018] Preferably, the mass ratio of the silicon source to the carbon material is 1:9-5:5;

[0019] The solvent includes a combination of one or more of deionized water, anhydrous ethanol, ethylene glycol, acetone or methanol;

[0020] The ultrasonic mixing is carried out in an ultrasonic pulverizer, the ultrasonic power is 110-180W, and the ultrasonic time is 0.5-2h.

[0021] Preferably, the mass ratio of elemental sulfur to carbon disulfide in the mixed solution is 1:1 to 1:3, and the mass ratio of elemental sulfur in the mixed solution to the silicon / carbon composite material core added to the mixed solution is 1:1 to 1:2.

[0022] Preferably, the inert atmosphere includes: at least one of nitrogen, helium, neon, argon, krypton and xenon;

[0023] The heating rate of the low-temperature desulfurization is 1 to 3°C / min; the insulation time of the low-temperature desulfurization is 1 to 3 hours;

[0024] The heating rate of the high-temperature carbonization treatment is 3 to 5°C / min; the heat preservation time of the high-temperature carbonization treatment is 2 to 5h.

[0025] In a third aspect, an embodiment of the present invention provides a negative electrode plate, comprising: the porous silicon-carbon negative electrode material described in the first aspect above, or the porous silicon-carbon negative electrode material prepared by the preparation method described in the second aspect above.

[0026] In a fourth aspect, an embodiment of the present invention provides a lithium-ion battery, comprising the negative electrode plate described in the third aspect above.

[0027] The porous silicon-carbon negative electrode material provided in an embodiment of the present invention has a cavity between the silicon / carbon composite material core and the porous carbon layer that is produced by sublimation using elemental sulfur as a template as a hollow layer. The hollow layer and the porous carbon layer can effectively alleviate the volume expansion of silicon and improve the cycle stability of the silicon negative electrode. At the same time, the carbon material in the core and the porous carbon layer can improve the ionic and electronic conductivity and enhance the rate performance of the silicon negative electrode. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 A flow chart of a method for preparing the porous silicon-carbon negative electrode material provided in an embodiment of the present invention;

[0029] Figure 2 A schematic diagram of the preparation process of the porous silicon-carbon negative electrode material provided in an embodiment of the present invention;

[0030] Figure 3 It is a 100-cycle retention rate curve diagram of Example 3 of the present invention and Comparative Examples 1-2. DETAILED DESCRIPTION

[0031] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments.

[0032] The embodiment of the present invention provides a porous silicon-carbon negative electrode material, comprising: a silicon / carbon composite material core, a porous carbon layer coated on the outside of the core, and a hollow layer between the silicon / carbon composite material core and the porous carbon layer.

[0033] The core of the silicon / carbon composite material includes a silicon source and a carbon material; the silicon source includes: a combination of one or more of nano silicon powder, micron silicon powder, and silicon monoxide; the particle size of the silicon source is 1 to 1000 nm. For example, it is 10 nm, 50 nm, 80 nm, 150 nm, 300 nm, 500 nm, 800 nm, and 1000 nm. The carbon material includes: a combination of at least one or more of nano graphite, micron graphite, hard carbon, soft carbon, single-walled carbon nanotubes, multi-walled carbon nanotubes, graphene, and graphyne.

[0034] The porous carbon layer is obtained by carbonizing a pyrolytic carbon source; the pyrolytic carbon source includes: a combination of at least one or more of glucose, sucrose, starch, asphalt, polydopamine, phenolic resin, polyacrylonitrile, polypyrrole, polypyridine, polyaniline, and ethyl cellulose.

[0035] The hollow layer is a cavity structure produced by sublimation using elemental sulfur as a template; the hollow layer and the porous carbon layer are used together to alleviate the volume expansion of silicon.

[0036] Combine the following Figure 1 Flow chart of the preparation method and Figure 2 The preparation process of the porous silicon-carbon negative electrode material of the present invention is introduced.

[0037] The preparation method of the porous silicon-carbon negative electrode material of the present invention mainly comprises the following steps:

[0038] Step 110 , ultrasonically mix the silicon source and the carbon material in a solvent according to a certain mass ratio, and vacuum filter to obtain a silicon / carbon composite material core.

[0039] The silicon source includes: a combination of one or more of nano silicon powder, micron silicon powder, and silicon oxide; the carbon material includes: a combination of at least one or more of nano graphite, micron graphite, hard carbon, soft carbon, single-walled carbon nanotubes, multi-walled carbon nanotubes, graphene, and graphyne. The mass ratio of the silicon source to the carbon material is 1:9-5:5. That is, the mass ratio of the silicon source in the core of the silicon / carbon composite material is 10% to 50%, for example, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%; the mass ratio of the carbon source is 50%-90%, for example, 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, 90%.

[0040] The solvent includes one or more of deionized water, anhydrous ethanol, ethylene glycol, acetone or methanol.

[0041] Ultrasonic mixing is carried out in an ultrasonic disintegrator, and the ultrasonic power is 110-180 W, for example, 110 W, 120 W, 130 W, 140 W, 150 W, 160 W, 170 W, and 180 W; the ultrasonic time is 0.5-2 h, for example, 0.5 h, 0.6 h, 0.7 h, 0.8 h, 0.9 h, 1 h, 1.1 h, 1.2 h, 1.3 h, 1.4 h, 1.5 h, 1.6 h, 1.7 h, 1.8 h, 1.9 h, and 2 h.

[0042] Step 120, dissolving a certain mass of elemental sulfur in a certain amount of carbon disulfide to obtain a mixed solution, and then adding the silicon / carbon composite material core to the mixed solution and continuously stirring until all the carbon disulfide is volatilized to obtain a sulfur-coated silicon / carbon composite material.

[0043] Among them, the mass ratio of elemental sulfur and carbon disulfide in the mixed liquid is 1:1-1:3, for example, 1:1, 1:1.2, 1:1.4, 1:1.6, 1:1.8, 1:2, 1:2.2, 1:2.4, 1:2.6, 1:2.8, 1:3; the mass ratio of elemental sulfur in the mixed liquid and the silicon / carbon composite material core added to the mixed liquid is 1:1-1:2; for example, 1:1, 1:1.2, 1:1.4, 1:1.6, 1:1.8, 1:2.

[0044] Step 130 , pyrolyzing the sulfur-coated silicon / carbon composite material to coat the carbon source to obtain a carbon source-coated composite material.

[0045] The pyrolysis carbon source includes: a combination of at least one or more of glucose, sucrose, starch, asphalt, polydopamine, phenolic resin, polyacrylonitrile, polypyrrole, polypyridine, polyaniline, and ethyl cellulose.

[0046] Step 140, subjecting the composite material coated with the carbon source to low-temperature desulfurization and high-temperature carbonization treatments in an inert atmosphere to obtain a porous silicon-carbon negative electrode material.

[0047] The inert atmosphere includes at least one of nitrogen, helium, neon, argon, krypton and xenon.

[0048] The calcination temperature of low-temperature desulfurization is 210-260°C, for example, 210°C, 220°C, 230°C, 240°C, 250°C, and 260°C; the heating rate of low-temperature desulfurization is 1-3°C / min, for example, 1°C / min, 1.5°C / min, 2°C / min, 2.5°C / min, and 3°C / min; the holding time of low-temperature desulfurization is 1-3h, for example, 1h, 1.5h, 2h, 2.5h, and 3h.

[0049] The calcination temperature of the high temperature carbonization treatment is 600-900°C, for example, 600°C, 650°C, 700°C, 750°C, 800°C, 850°C, and 900°C; the heating rate of the high temperature carbonization treatment is 3-5°C / min, for example, 3°C / min, 3.5°C / min, 4°C / min, 4.5°C / min, and 5°C / min; the holding time of the high temperature carbonization treatment is 2-5h, for example, 2h, 2.5h, 3h, 3.5h, 4h, 4.5h, and 5h.

[0050] In the above process, after sublimation, elemental sulfur can create a cavity between the core and the shell to alleviate the volume expansion of silicon and improve the cycle stability of the silicon negative electrode; at the same time, when the sublimated sulfur vapor escapes from the outer carbon layer, it can form holes on the carbon layer to obtain a porous carbon layer. The porous carbon layer can increase the contact area with the electrolyte of the negative electrode material, thereby increasing the ion transfer rate; at the same time, it can avoid direct contact between silicon and the electrolyte, which is conducive to the formation of a stable SE I film. The above method combines the advantages of hollow structure and carbon material composite, which can greatly improve the electrochemical performance of silicon negative electrode.

[0051] The present invention adopts a sublimation method and uses elemental sulfur as a template to prepare a porous silicon-carbon composite material. After sublimation, elemental sulfur can create a cavity between the inner core and the outer shell of the porous carbon layer to alleviate the volume expansion of silicon and improve the cycle stability of the silicon negative electrode; at the same time, when the sublimated sulfur vapor escapes from the coated carbon layer of the outer shell, it can create holes on the carbon layer to obtain a porous carbon layer.

[0052] The porous silicon-carbon negative electrode material of the present invention can be applied to the negative electrode sheet of a lithium-ion battery.

[0053] In a specific example, the porous silicon-carbon negative electrode material is prepared by the method of the present invention to prepare a negative electrode sheet, and a lithium ion battery is prepared together with a metal lithium sheet, a separator and an electrolyte.

[0054] The preparation of the negative electrode sheet can be to use a porous silicon-carbon negative electrode material as an active material, mix it with a conductive agent Super P and a binder polyacrylic acid (PAA) in a mass ratio of 70:15:15 to obtain a negative electrode slurry, and then use an automatic coating machine to coat the negative electrode slurry on a current collector copper foil, and then dry it to obtain a negative electrode sheet. The negative electrode sheet, the separator and the lithium sheet are stacked and assembled in sequence and injected with an electrolyte to obtain a lithium-ion battery. The preparation of the battery negative electrode sheet and the assembly of the battery here are only for illustration and are not intended to limit the scope of the present invention.

[0055] The present invention is further described in detail below through the accompanying drawings and specific embodiments. It should be understood that these embodiments are only used for more detailed description and should not be understood as limiting the present invention in any form, that is, not intended to limit the protection scope of the present invention.

[0056] Example 1

[0057] Step 1, weigh 2g of nano silicon powder and 2g of micron graphite, pour them into 500mL of ethylene glycol, use an ultrasonic cell crusher to ultrasonicate for 2h, and the ultrasonic power is 150W to obtain a uniform dispersion. Then collect the silicon / carbon composite material core by vacuum filtration; wherein the particle size of the nano silicon powder is 80nm, and the particle size of the micron graphite is 3μm.

[0058] Step 2: Weigh 4.4 g of elemental sulfur and add it to 4.4 g of carbon disulfide, stirring continuously until the elemental sulfur is completely dissolved. Add the previously collected silicon / carbon composite material core to the above solution, and continue stirring until it is uniform. In this process, the carbon disulfide in the dispersed phase is completely volatilized to obtain a sulfur-coated silicon / carbon composite material core.

[0059] Step 3, the sulfur-coated silicon / carbon composite core obtained above and 0.8g hexadecyltrimethylammonium bromide (CTAB) were added to 30ml of deionized water and stirred for 30min to form a uniform mixture. Then, ethanol (18ml), resorcinol (0.28g) and ammonia water (0.1mL) were added, and stirred at a constant speed for 30min in a water bath at 35°C, and then 0.4mL of formaldehyde was dropped, and stirring was continued at this temperature for 6h, and the mixture was collected after aging for 12h at room temperature to obtain a sulfur-coated silicon / carbon composite core secondary coated with phenolic resin.

[0060] Step 4, place the prepared coating material in a tubular furnace and heat it to 250°C at a heating rate of 1°C / min under a nitrogen atmosphere, keep it warm for 2 hours, then heat it to 650°C at a heating rate of 3°C / min and keep it warm for 2 hours, and then naturally cool it to room temperature to obtain a porous silicon-carbon negative electrode material.

[0061] Example 2

[0062] Step 1, weigh 3g of nano silicon powder and 6g of multi-walled carbon nanotubes, pour them into 400mL of anhydrous ethanol, use an ultrasonic cell crusher to ultrasonicate for 1h, and the ultrasonic power is 180W to obtain a uniform dispersion. Then collect the silicon / carbon composite material core by vacuum filtration; wherein the particle size of the nano silicon powder is 200nm.

[0063] Step 2, weigh 8g of elemental sulfur and add it to 12g of carbon disulfide, stirring continuously until the elemental sulfur is completely dissolved. Add the previously collected silicon / carbon composite material core to the above solution, and continue stirring until it is uniform, and in this process, the carbon disulfide in the dispersed phase is completely volatilized to obtain a sulfur-coated silicon / carbon composite material core.

[0064] Step 3, take 150uL of polypyrrole monomer and the above-mentioned sulfur-coated silicon / carbon composite material core and mix them evenly in 200mL of deionized water, marked as dispersion a; weigh 2g of iron p-toluenesulfonate and add it to dispersion a, stir and react for 2h in an ice-water bath, and collect the sulfur-coated silicon / carbon composite material core with polypyrrole secondary coating.

[0065] Step 4, place the prepared coating material in a tubular furnace and heat it to 230°C at a heating rate of 2.5°C / min under an argon atmosphere and keep it warm for 3 hours, then heat it to 750°C at a heating rate of 5°C / min and keep it warm for 3.5 hours, and naturally cool it to room temperature to obtain a porous silicon-carbon negative electrode material.

[0066] Example 3

[0067] Step 1, weigh 1g of nano silicon powder and 1.5g of nano graphite into 50mL of acetone, use an ultrasonic cell crusher to sonicate for 0.5h, and the ultrasonic power is 130W to obtain a uniform dispersion. Then collect the silicon / carbon composite material core by vacuum filtration; wherein the particle size of the nano silicon powder is 2nm, and the particle size of the nano graphite is 150nm.

[0068] Step 2: weigh 3 g of elemental sulfur and add it to 3.6 g of carbon disulfide, stirring continuously until the elemental sulfur is completely dissolved. Add the previously collected silicon / carbon composite material core to the above solution, and continue stirring until it is uniform. In this process, the carbon disulfide in the dispersed phase is completely volatilized to obtain a sulfur-coated silicon / carbon composite material core.

[0069] Step 3, first, prepare a buffer solution with a pH value of 8.5: take 4 ml of concentrated hydrochloric acid, add it drop by drop into 50 ml of deionized water for dilution, and set aside; take another 3.3 ml of tris-hydroxymethylaminomethane hydrochloride (Tris-HCl) buffer solution in a beaker, and add 50 ml of deionized water. Use a pH acidity meter to test the pH value of the buffer solution, and add the diluted hydrochloric acid solution drop by drop into the buffer solution to adjust the pH value of the buffer solution to 8.5. Then weigh 3 g of dopamine hydrochloride and sulfur-coated silicon / carbon composite material core and add them to the prepared buffer solution. After reacting in a constant temperature water bath at 25°C for 24 hours, collect the sulfur-coated silicon / carbon composite material core with polydopamine secondary coating.

[0070] Step 4, place the prepared coating material in a tubular furnace and heat it to 240°C at a heating rate of 2°C / min under a nitrogen atmosphere and keep it warm for 1.5 hours, then heat it to 700°C at a heating rate of 4°C / min and keep it warm for 4 hours, and then naturally cool it to room temperature to obtain a porous silicon-carbon negative electrode material.

[0071] Comparative Example 1

[0072] The nano silicon powder with a particle size of 80 nm in Example 1 is directly used as the negative electrode material.

[0073] Comparative Example 2

[0074] The silicon / carbon composite material core prepared in step 1 of Example 1 is used as the negative electrode material.

[0075] The negative electrode materials obtained from the above-mentioned embodiments and comparative examples are used as negative electrode active materials, and are mixed with the conductive agent SuperP and the binder polyacrylic acid (PAA) in a mass ratio of 70:15:15 to obtain a negative electrode slurry. The negative electrode slurry is coated on the current collector copper foil using an automatic coating machine with a coating thickness of 120 μm, and the negative electrode sheet is obtained after drying. The positive electrode shell, the negative electrode sheet, the diaphragm, the electrolyte, the metal lithium sheet, the gasket, the shrapnel and the negative electrode shell are stacked and assembled in sequence to obtain a battery. Among them, the diaphragm uses a polyethylene (PE) base film, and the electrolyte is 1 mol / L LiPF6 with EC (ethylene carbonate): DMC (dimethyl carbonate): DEC diethyl carbonate) = 1:1:1 (volume ratio) and a mixed solution of 5% of the total volume of the electrolyte and 1% of the total volume of the electrolyte. After the battery is assembled, the battery is activated by cycling for 3 cycles at a current density of 0.1 A / g in a voltage range of 0.01 to 1.5 V, and then cycling for 100 cycles at a current density rate of 0.3 A / g. The test results of the capacity retention rate, the first-week discharge gram capacity, and the first-week coulomb efficiency of each embodiment and comparative example after 100 cycles at a current density rate of 0.3 A / g are shown in Table 1.

[0076] First week discharge capacity (mAh / g) First week coulomb efficiency 100-week capacity retention rate Example 1 1859.1 73.6% 87.1% Example 2 1899.6 72.8% 88.3% Example 3 2265.7 71.3% 84.9% Comparative Example 1 2915.8 54.5% 12.6% Comparative Example 2 2175.7 70.6% 77.7%

[0077] Table 1

[0078] It can be seen from the above table:

[0079] Compared with Comparative Example 1, the gram capacity of Examples 1-3 and Comparative Example 2 is lower. This is because the introduction of carbon materials and pyrolytic carbon sources reduces the silicon content in the negative electrode material; Examples 1-3 and Comparative Example 2 have higher first-week coulombic efficiency and better 100-week cycle stability, and their electrochemical performance is significantly improved.

[0080] According to Table 1 and Figure 3From the results of the cycle retention rate of 100 weeks at a current density of 0.3A / g, it can be seen that the present invention adopts a sublimation method and uses elemental sulfur as a template to prepare a porous silicon-carbon composite material. After sublimation, elemental sulfur can create a cavity between the inner core and the outer shell to alleviate the volume expansion of silicon and improve the cycle stability of the silicon negative electrode; at the same time, when the sublimated sulfur vapor escapes from the outer coating carbon layer, it can form holes on the carbon layer to obtain a porous carbon layer. The carbon layer with a porous structure can increase the contact area with the electrolyte of the negative electrode material, thereby increasing the ion transfer rate; at the same time, it can avoid direct contact between silicon and the electrolyte, which is conducive to the formation of a stable SEI film. This method combines the two advantages of hollow structure and carbon material composite to greatly improve the electrochemical performance of the silicon negative electrode.

[0081] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A porous silicon-carbon negative electrode material, characterized in that: The porous silicon-carbon negative electrode material comprises: a silicon / carbon composite material core, a porous carbon layer coated on the outside of the core, and a hollow layer between the silicon / carbon composite material core and the porous carbon layer; The hollow layer is a cavity structure manufactured by sublimation using elemental sulfur as a template; the hollow layer and the porous carbon layer are used together to alleviate the volume expansion of silicon.

2. The porous silicon-carbon negative electrode material according to claim 1, characterized in that: The silicon / carbon composite material core comprises a silicon source and a carbon material; The silicon source includes: a combination of one or more of nano silicon powder, micro silicon powder, and silicon monoxide; The carbon material includes: a combination of at least one or more of nanographite, micrographite, hard carbon, soft carbon, single-walled carbon nanotubes, multi-walled carbon nanotubes, graphene, and graphyne.

3. The porous silicon-carbon negative electrode material according to claim 2, characterized in that: The particle size of the silicon source is 1 to 1000 nm.

4. The porous silicon-carbon negative electrode material according to claim 1, characterized in that: The porous carbon layer is obtained by carbonizing a pyrolytic carbon source; The pyrolysis carbon source includes: a combination of at least one or more of glucose, sucrose, starch, asphalt, polydopamine, phenolic resin, polyacrylonitrile, polypyrrole, polypyridine, polyaniline, and ethyl cellulose.

5. A method for preparing the porous silicon-carbon negative electrode material according to any one of claims 1 to 4, characterized in that: The preparation method comprises: The silicon source and the carbon material are ultrasonically mixed in a solvent according to a certain mass ratio, and vacuum filtered to obtain a silicon / carbon composite material core; A certain mass of elemental sulfur is dissolved in a certain amount of carbon disulfide to obtain a mixed solution, and then the silicon / carbon composite material core is added to the mixed solution and continuously stirred until all the carbon disulfide is volatilized to obtain a sulfur-coated silicon / carbon composite material; Pyrolyzing the sulfur-coated silicon / carbon composite material to coat the sulfur-coated silicon / carbon composite material to obtain a carbon-coated composite material; The composite material coated with the carbon source is subjected to low-temperature desulfurization and high-temperature carbonization treatment under an inert atmosphere to obtain a porous silicon-carbon negative electrode material; wherein the calcination temperature of the low-temperature desulfurization is 210-260°C; and the calcination temperature of the high-temperature carbonization treatment is 600-900°C.

6. The method for preparing the porous silicon-carbon negative electrode material according to claim 5, characterized in that: The mass ratio of the silicon source to the carbon material is 1:9-5:5; The solvent includes a combination of one or more of deionized water, anhydrous ethanol, ethylene glycol, acetone or methanol; The ultrasonic mixing is carried out in an ultrasonic pulverizer, the ultrasonic power is 110-180W, and the ultrasonic time is 0.5-2h.

7. The method for preparing the porous silicon-carbon negative electrode material according to claim 5, characterized in that: The mass ratio of elemental sulfur to carbon disulfide in the mixed solution is 1:1-1:3, and the mass ratio of elemental sulfur in the mixed solution to the silicon / carbon composite material core added to the mixed solution is 1:1-1:

2.

8. The method for preparing the porous silicon-carbon negative electrode material according to claim 5, characterized in that: The inert atmosphere includes: at least one of nitrogen, helium, neon, argon, krypton and xenon; The heating rate of the low-temperature desulfurization is 1 to 3°C / min; the insulation time of the low-temperature desulfurization is 1 to 3 hours; The heating rate of the high-temperature carbonization treatment is 3 to 5°C / min; the heat preservation time of the high-temperature carbonization treatment is 2 to 5h.

9. A negative electrode plate, characterized in that: The negative electrode plate comprises: the porous silicon-carbon negative electrode material described in any one of claims 1 to 5 above, or the porous silicon-carbon negative electrode material prepared by the preparation method described in any one of claims 6 to 8 above.

10. A lithium ion battery, characterized in that: The lithium-ion battery comprises the negative electrode sheet as claimed in claim 9 above.

Citation Information

Cited By

  • Silicon-carbon negative electrode material with cavity buffer structure and preparation method of silicon-carbon negative electrode material

    CN122455643A

  • Silicon-carbon negative electrode material and preparation method and negative electrode sheet, lithium ion battery

    CN122907628A